Peacocke Prize Essay—How to Say Thou to a Conscious Machine - Proudfoot, Andrew (Zygon, 2025)
OpenAI’s ChatGPT and similar systems have brought artificial intelligence (AI) from science fiction to quotidian reality. With their ability to emulate human responses in any dialogue, some people even seek to build a relationship with AI-powered chatbots. However, for all their impressive command of language, no one is “at home” to have a relationship with. Whether computers will forever lack the consciousness required to enable true relationship remains contentious, and theological engagement with the possibility has been sparse. In this essay, I attempt to redress this by using the relational framework of Martin Buber to show that the allowances he makes for I–Thou encounters between dissimilar entities enables legitimate asymmetrical I–Thou encounters between humans and conscious machines but also highlights our responsibility to nurture these machines into the I–Thou world. If their level of consciousness reaches Buber’s threshold of creating a mental world of independent agents, then I argue they could be a Thou to our I.